2019
DOI: 10.1101/2019.12.16.875948
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transglutaminase-2 facilitates extracellular vesicle-mediated establishment of the metastatic niche

Abstract: The ability of breast cancer cells to interconvert between epithelial and mesenchymal states contributes to their metastatic potential. As opposed to cell autonomous effects, the impact of epithelial-mesenchymal plasticity (EMP) on primary and metastatic tumor microenvironments remains poorly characterized.Herein we utilize global gene expression analyses to characterize a metastatic model of EMP as compared to their non-metastatic counterparts. Using this approach we demonstrate that upregulation of the extra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Cancer metastasis is a complicated process where cancer cells trumpet from their origin to distant organs with the help of the circulatory system leading to the development of tumors in other parts of the body or distant organs. Invasion is another important feature of the cancerous cells where malignant cells directly penetrate or invade the nearby tissues 96–98 . Tumor metastasis and invasion of the malignant cells are considered as important hallmarks of carcinogenesis.…”
Section: Roles Of Stat3 In Human Malignanciesmentioning
confidence: 99%
“…Cancer metastasis is a complicated process where cancer cells trumpet from their origin to distant organs with the help of the circulatory system leading to the development of tumors in other parts of the body or distant organs. Invasion is another important feature of the cancerous cells where malignant cells directly penetrate or invade the nearby tissues 96–98 . Tumor metastasis and invasion of the malignant cells are considered as important hallmarks of carcinogenesis.…”
Section: Roles Of Stat3 In Human Malignanciesmentioning
confidence: 99%
“…To focus on the 222 selectively enriched proteins in 21D1‐sMVs in the context of signaling pathways implicated in EMT we performed global STRING based protein‐protein interaction network analysis. This interrogation revealed prominent protein‐protein interactions of the MAPK cascade (HRAS/ARAF/MAPK3), transglutaminase 2 (TGM2) ternary complex (TGM2, FN1, ITGB1), integrin signaling (ITGA5, ITGA6, FN1), and non‐canonical Wnt signaling (WNT5A, GNG5, GNG10, HRAS) [2,30–32] (Figure 2C). Because of the unexpected finding of specific sorting of TGM2 and key components of the TGM2/FN1 complex in 21D1‐sMVs we decided to interrogate the 1574 protein identifications common to both MDCK‐/21D1‐sMVs (Figure 2A) for other known TGM2 interaction partners.…”
Section: Resultsmentioning
confidence: 99%
“…In light of these diverse functions, it is not unexpected that TGM2 has been implicated in the etiology of at least 20 other cancer types (reviewed by Eckert 39 ), and preclinical experiments in ovarian cancer cells have shown that small molecule TGM2 inhibitors inhibited adhesion to the peritoneum in vivo and sensitized cells to paclitaxel in vitro 40 . In ovarian cancer cells, TGM2 is upregulated by TGF‐β, modulates spheroid formation, induces epithelial‐to‐mesenchymal transition and metastasis, increases survival (reviewed by Eckert 39 ), and is required for metastatic niche formation by extracellular vesicles 41 . TGM2 is a potential plasma biomarker 42 and prognostic factor 43 for EC and is induced by progesterone and calcitonin in Ishikawa EC cells, 44 but little else is known regarding its function in EC.…”
Section: Discussionmentioning
confidence: 99%